Selective Adsorption Behaviour of Mesoporous Silica SBA-15-N-Acetylcysteine Imprinted Polymer Based on Surface Molecular Imprinting Technique - Zhu, Xiaolan; Zhu, Qingsheng; Yang, Jun; Gao, Yun (Asian Journal of Chemistry, 2014)
A new N-acetylcysteine ion-imprinted polymer (NAC-MIP), which can be used for selective adsorption of N-acetylcysteine from aqueous solutions, was successfully prepared based on the supported material of ordered mesoporous silica SBA-15 with the help of surface molecular imprinting technology. The prepared polymer was characterized by Fourier transmission infrared sepectrometry, X-ray diffraction, scanning electron microscopy and 13C NMR spectroscopy. The results showed that the synthesized polymer possessed highly ordered mesoporous structure. The imprinted silica particle showed high selectivity and fast kinetic binding for the template due to its nanosized wall thickness and high surface area.